Evaluation of the application of a thermostable Newcastle disease vaccine by community volunteers in the North West Province - Bisschop, Shahn P.R. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2007.